The use of self-determination theory to investigate career aspiration, choice of major and academic achievement of tertiary science students. Issue 10 (2nd July 2020) - Rayner, Gerry; Papakonstantinou, Theo
ABSTRACT: This study investigated the interrelationships among university entrance score, career aspiration, academic major, and academic achievement, of foundation year students, at an overall level and at completion of each year level of a Bachelor of Science (BSc) degree. Self-determination theory (SDT) was used as the underlying model for this study, which comprised 157 students who had completed their degree over 2015–2017. Results were analysed in terms of students' intrinsic motivations (career aspiration and academic major), extrinsic motivations (university entrance score and academic success) and an amotivational factor (gender). We propose a model to explain the observed change in importance between BSc students' extrinsic and intrinsic motivations, as a function of time and their increasing autonomy. If our results reflect broader patterns among Australian students undertaking post-secondary education, the use of grounded SDT-based approaches during foundation year may allow students to make more informed choices of academic major, and through this enhance their academic achievement.